Creamos un collage sobre el deterioro del medio ambiente - Gonzales Pérez, Carlos (2018)
The learning session has been made with the technique of photographic collage and with the theme of the deterioration of the environment, has used pedagogical processes such as motivation, exploration of knowledge, cognitive conflict, management and monitoring, evaluation and evaluation of the product ._x000D_ Collage is a technique that assembles graphic languages of different natures, completely open and free, that has no limitations, recycled material, Internet images, newspapers and magazines about the environment and the obvious signs of deterioration in the soil have been used. air and water to generate reflection, appreciation and commitment. Likewise, teamwork has been promoted, where the respect and collaboration of all its members was promoted._x000D_ The learning session achieved the attention of the students allowing them to create useful artistic languages for the management and expression of their emotions, it is suggested to continue exploring and developing this technique that allows the development of creativity and expression in its multiple forms, besides it can be Work on this subject in any grade of regular basic education.